LEVERS FOR THE MACROSTABILIZATION OF ECONOMY AVAILABLE TO THE MONETARY AUTHORITY AND ACTUAL MEASURES ADOPTED IN THE CONTEXT OF THE COVID-19 PANDEMIC - Mădălina RĂDOI; Nicoleta PANAIT (Challenges of the Knowledge Society)
Measures taken by states, in the context of epidemiological situation, to reduce the effects of the health crisis have been severe, the most important being stopping non-essential activities, restricting travel and banning travel to and from certain countries and causing shocks in production and distribution chains, but also a sharp contraction in demand for a wide range of goods and services. Given the difficult economic context created by the COVID-19 pandemic, which impacted both the national and global economy, one of the objectives adopted by the Romanian monetary authority in the first half of 2020 was to maintain the stability and liquidity of the banking system for proper functioning of public finance and the real economy. As a state of emergency was declared as of March 16 2020, and considering that the main fiscal response in Romania came from the national budget, the NBR collaborated with the Government in order to avoid a potential conflict between government measures and fiscal measures. One of the unconventional measures "quantitative easing" which involves the basic injection of money into the market in exchange for various financial assets was used by the monetary authorities, including in emerging economies, such as NBR. This paper focuses on the measures and effectiveness of the monetary policy of the national monetary authority in order to reduce the negative effects of the crisis caused by the COVID-19 pandemic.